Preparation method of road water stabilizing layer filler based on steel slag recycling
By pretreating and modifying the steel slag, composite particles are formed, and molding is performed by microwave + far-infrared combination heating and wheel milling method, the compactness, permeability and volume expansion of the steel slag water stabilized layer filler is solved, and the problem of the steel slag water stabilized layer filler is achieved. Efficient preparation of road water-stabilizing layer filler.
Patent Information
- Application Number
- CN202410841771.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The existing preparation methods for steel slag recycling and utilization road water-stabilizing layer fillers have problems such as poor compactness, harmful volume expansion and insufficient water permeability.
By pretreating and modifying the steel slag, including crushing into various particle sizes, carbonization, using deionized water and silane coupling agents, forming composite particles, and forming by microwave + far infrared combined heating and wheel milling method. Improve the density and water permeability of the material.
It improves the bearing capacity, stability and water permeability of the steel slag water stabilized layer filler, reduces the harm of volume expansion, extends the service life of the road and reduces construction costs.
Smart Images

Figure CN119143430A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel slag recycling, and specifically is a method for preparing road water-stabilizing layer filler based on steel slag recycling. Background Art
[0002] Steel slag is an industrial byproduct produced during the steel smelting process, mainly composed of silicate, calcium oxide, magnesium oxide, aluminum oxide and a small amount of sulfide and phosphide. The recycling of steel slag is of great significance. It can not only reduce environmental pollution, but also be converted into valuable resources.
[0003] Steel slag can be crushed and screened and used as road base or surface material. Due to its good mechanical properties and durability, road materials made of steel slag can improve the load-bearing capacity and service life of roads. Using steel slag as road construction material can reduce the cost of raw material procurement, while reducing the cost of steel slag treatment and disposal, which has economic benefits for both enterprises and society. The recycling of steel slag is in line with the concept of green development and circular economy, and helps promote the sustainable development of the construction industry and materials science.
[0004] Therefore, there is an urgent need for a method for preparing road water-stabilizing layer filler based on steel slag recycling. The existing preparation method has the following defects: the steel slag is crushed into a uniform particle size, which easily leads to poor overall density of the prepared filler. At the same time, the steel slag is prone to volume expansion, and local expansion hazards will occur when applied to the road base, and the overall water permeability of the prepared road water-stabilizing layer filler is poor. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention provides a method for preparing a road water-stabilizing layer filler based on steel slag recycling.
[0006] The technical solution of the present invention is: a method for preparing a road water-stabilizing layer filler based on steel slag recycling, comprising the following steps:
[0007] S1. Pretreatment of slag
[0008] First, the steel slag is washed with tap water, and then dried to obtain clean steel slag base material. After the steel slag base material is crushed by a crusher, it is placed in a carbonization box for carbonization treatment for 45-50 hours to obtain steel carbonized particles. Then, the steel carbonized particles are dried and ball-milled until the specific surface area of the steel carbonized particles is 150-180m 2 / kg;
[0009] S2. Modification of steel slag
[0010] The steel carbonized particles after ball milling, deionized water and fly ash are mixed, granulated and dried in a mass ratio of 2:0.5 to 1:0.25 to obtain steel carbonized green balls; anhydrous ethanol, expanded glass microspheres and steel carbonized green balls are uniformly mixed in a mass ratio of 1:0.6:1, and 1.2-1.5wt% silane coupling agent is added thereto; the pH is adjusted to 7.5-8, and the mixture is heated and freeze-dried to obtain steel slag modified particles; then, the steel slag modified particles, silicone oil and methyl methacrylate are mixed in a weight ratio of 1:3:4 to obtain steel slag modified particles; methyl acrylate is mixed evenly to form a first premix, then, deionized water, sodium dodecylbenzene sulfonate and sodium bicarbonate are mixed evenly in a weight ratio of 8:3:0.2 to form a second premix, and then, the first premix and the second premix are mixed in a weight ratio of 1:2, ultrasonic fine emulsification is performed at room temperature for 20-25 minutes, and 1-1.5wt% of azobisisobutyronitrile is added thereto, stirred evenly, and placed in a water bath at a temperature of 80-85°C for 2-3 hours, and cooled to room temperature to obtain steel slag composite particles;
[0011] S3. Preparation of filler
[0012] According to weight parts, 35-60 parts of steel slag composite particles, 5-15 parts of cement, 5-15 parts of granite powder, 3-5 parts of lime and 30-50 parts of water are mixed until uniform, and heated at a temperature of 160-170° C. for 3-5 hours to obtain a filler blank, and then the temperature is raised to 200-220° C. At the same time, 1-2 parts of stabilizer are added to the filler blank, and sheared for 10-15 minutes to obtain a filler pre-finished product, wherein the temperature controlled at 160-170° C. refers to the initial temperature before the reaction, that is, at Before lime and water start to react significantly and release heat, the purpose is to ensure that the mixed material can be preliminarily heated in a relatively stable temperature environment. During the heating process, cement will begin to hydrate after adding water, and lime (calcium oxide CaO) will react with water to form calcium hydroxide (Ca(OH)2). After heating to 200-220℃ and adding stabilizer, the above reaction will be further promoted, which will help improve the thermal stability and durability of the material. The shearing process will help break up the agglomerates inside the material, making it more uniform and delicate.
[0013] S4, Forming and Compacting
[0014] The wheel rolling method is adopted to pre-press the filler pre-finished product 4-5 times, and finally, the direction is changed and rolled 5-10 times to obtain the filler finished product.
[0015] Furthermore, in step S1, after the steel slag base material is crushed by a crusher, a vibrating screen is used to take steel slag particles with particle sizes in the ranges of 0.5-1.5 mm, 1.6-2.5 mm, and 2.6-4 mm, respectively, and the surface of the steel slag particles in each particle size range is sprayed with a water reducer, and then placed in a carbonization box. When the vacuum degree is -0.25 MPa, CO2 gas is introduced until the pressure value in the carbonization box reaches 0.25 MPa, and then, after carbonization treatment, steel carbonized particles are obtained.
[0016] Description: The steel slag base material is crushed into steel slag particles of different sizes, and the steel slags of different sizes can be embedded in each other, which helps to improve the overall density of the mixture. Steel slags of various sizes can form a more complex skeleton structure after mixing, which helps to improve the bearing capacity and stability of the water-stabilizing layer filler. The crushed steel slag particles are carbonized, so that the active ingredients in the steel slag, such as calcium oxide, react with carbon dioxide to form calcium carbonate, thereby improving the stability and durability of the steel slag. The calcium carbonate generated during the carbonization process fills the gaps between the steel slag particles, increases the density of the material, and improves its compressive strength and flexural strength. During the carbonization treatment, the surface tension of water can be reduced by spraying a water reducer on the surface of the steel slag particles, making it easier for water to penetrate between the steel slag particles.
[0017] Furthermore, the water reducer is a polycarboxylic acid water reducer selected from one of methacrylic acid, acrylic acid, acrylamide or hydroxypropyl methylcellulose.
[0018] Description: Polycarboxylate water reducer can significantly reduce the water content of concrete without affecting its workability, usually reducing water by 5% to 30%.
[0019] Furthermore, in step S2, the temperature of the deionized water is 60-90° C., and the silane coupling agent is MPS or ODMS.
[0020] Description: The temperature of deionized water is controlled within the range of 60-90°C. Through the pre-treatment of deionized water and steel carbonized particles in this temperature range, the generated hydration products can form a dense protective layer on the surface of steel slag, preventing the steel slag from further hydration, improving the volume stability of the steel slag, and gradually reducing the volume expansion of the steel slag, thereby reducing the probability of local expansion hazards in the road base.
[0021] Furthermore, in step S3, a microwave + far infrared combination heating method is used for the mixture of steel slag composite particles, cement, granite powder, lime and water, wherein the microwave + far infrared combination is performed in an intermittent heating manner.
[0022] Description: Microwave heating has the advantages of fast heating speed and uniform heating, and can quickly increase the temperature of the material; far-infrared heating transfers heat energy through infrared radiation, which is suitable for surface heating and deep heating. Microwave heating can promote the polarization and rapid movement of water molecules, accelerate the hydration reaction between cement and water, the digestion reaction between lime and water, and the hydration reaction between steel slag composite particles and granite powder and water. Far-infrared heating helps maintain the structural stability of the material, reduces the volume expansion and contraction caused by rapid hydration reactions, and helps reduce the risk of cracks in the road water-stabilizing layer filler.
[0023] Furthermore, the intermittent heating process is: heating with microwave for 35-40 seconds, cooling with heat exchanger for 2-3 minutes, heating with far infrared for 40-45 seconds, cooling with heat exchanger for 2-3 minutes, this is one cycle, and the operation is repeated 3-4 times until the mixture of steel slag composite particles, cement, granite powder, lime and water is heated to 120-140° C., and finally, it is kept warm for 30-35 minutes.
[0024] Description: By alternately using microwave and far-infrared heating, and utilizing the characteristics of microwave rapid heating and the advantages of far-infrared deep heating, it is possible to ensure more precise temperature control during the heating process, reduce volume expansion and contraction caused by rapid hydration reactions, improve heating efficiency, and ensure material quality. In the heating process, during the microwave + far-infrared intermittent heating process, in the first cycle of microwave heating, the mixture of lime and water will heat up rapidly and begin to react chemically. Subsequently, in the far-infrared heating stage, although the temperature drops slightly, the mixture of lime and water is still within a higher temperature range, so the reaction continues. In the cooling stage between each microwave heating and far-infrared heating, the temperature of the mixture decreases, which may slow down the reaction rate. However, due to the entire heating process The process is repeated, and the mixture as a whole will be kept in a higher temperature range, which is sufficient to maintain the digestion process of lime and other related hydration reactions. After the entire intermittent heating process is completed, the step of keeping warm for 30-35 minutes is to ensure that all reactions can be fully carried out, including the complete digestion of lime and the hydration reaction between cement and other components. During this period of time, even if the initial rapid reaction has been completed, the remaining reactants will continue to react, thereby ensuring that the mixture achieves the desired physical and chemical properties. Therefore, although the reaction of lime and water begins at the beginning of the heating process and continues in subsequent heating cycles, the entire intermittent heating process is designed to be sufficient to ensure the complete reaction of lime and water and that the mixture finally reaches a suitable hardened state.
[0025] Furthermore, the microwave frequency is 2.35-2.45 GHz, the far infrared wavelength is 50-80 μm, and the heating time is 1.2-1.5 h.
[0026] Description: By precisely controlling the power, frequency and heating time of microwaves and far infrared, the heating process can be optimized and the risk of overheating and uneven heating can be reduced.
[0027] Furthermore, in step S4, the filler pre-finished product is subjected to curing treatment before pre-pressing, and the curing process is as follows:
[0028] S4-1, curing the filler blank at a temperature of 30-35°C for 12-13 hours;
[0029] S4-2, using steam curing, the curing temperature is 95-100 ° C, the curing time is 3-4 hours, and the room temperature curing process is performed again, and the curing time is controlled to be 5-6 hours, and the steam curing process is repeated, and the curing is alternately performed 2-3 times to obtain a finished curing filler product;
[0030] S4-3, spray water on the filler curing product for 6-7 hours, and the amount of water sprayed is 12-13% of the weight of the filler curing product, and finally air-dry.
[0031] Description: The filler blank is cured in sections by alternating between room temperature curing and high-temperature steam curing. This combines the advantages of high-temperature rapid hardening with the effect of long-term stable curing at room temperature, which can reduce the rapid evaporation of water, avoid cracks on the road surface prepared by the filler, and improve the performance and quality of the filler blank.
[0032] Furthermore, during steam curing in step S4-2, the heating rate of steam is 4-5°C / min.
[0033] Note: By controlling the heating rate of steam, it is possible to avoid the possibility that the heating rate is too fast, which may cause thermal stress inside the packing and cause cracks.
[0034] Compared with the prior art, the beneficial effects of the present invention are:
[0035] The road water-stabilizing layer filler of the present invention is made by recycling steel slag as a basic raw material. While solving the environmental pollution problem caused by improper treatment of steel slag, it also reduces the cost of road construction. The steel slag of the present invention is pretreated and modified on the existing basis, overcoming the potential volume expansion of steel slag and avoiding the local expansion hazard when applied to the road base. During the pretreatment, the steel slag is crushed into particles of various particle sizes in order to allow the steel slag particles of various particle sizes to be mutually embedded, which helps to improve the overall density of the mixture. At the same time, the crushed steel slag particles are carbonized, so that the active components in the steel slag, such as calcium oxide, react with carbon dioxide to generate calcium carbonate, thereby improving the stability and durability of the steel slag. The calcium carbonate generated during the carbonization process fills the steel slag. The gaps between the particles increase the density of the material and improve its compressive strength and flexural strength. During the modification treatment, deionized water and the steel carbonized particles can be prevented from further hydration, thereby reducing the expansion of the steel slag and improving the volume stability of the steel slag. After the steel slag is pretreated with fly ash, needle-shaped and spatial network products will be generated. At the same time, the products are wrapped on the surface of the steel slag to form a protective layer, which further reduces the expansion of the steel slag. A chemical bond bridge can be formed between the steel carbonized raw balls and the expanded glass microspheres through the silane coupling agent, thereby improving the compatibility and bonding strength of the two. At the same time, the expanded glass microspheres can form an open pore structure in the steel carbonized raw balls. These pores provide channels for water, allowing water to pass through the steel slag composite particles, thereby improving the overall permeability of the road water-stabilizing layer filler. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0037] In order to further understand the content of the present invention, the present invention is described in detail below through examples.
[0038] Example 1
[0039] A method for preparing a road water-stabilizing layer filler based on steel slag recycling comprises the following steps:
[0040] S1. Pretreatment of slag
[0041] The steel slag was first rinsed with tap water and then dried to obtain a clean steel slag base material. The steel slag base material was crushed by a crusher, and steel slag particles with particle sizes of 0.5 mm, 1.6 mm, and 2.6 mm were taken using a vibrating screen. The surface of the steel slag particles in each particle size range was sprayed with a water reducer, and then placed in a carbonization box. When the vacuum degree was -0.25 MPa, CO2 gas was introduced until the pressure in the carbonization box reached 0.25 MPa. The carbonization treatment was performed for 45 hours to obtain steel carbonized particles. Then, the steel carbonized particles were dried and ball-milled until the specific surface area of the steel carbonized particles was 150 m 2 / kg, washing the steel slag can remove harmful substances in the steel slag, such as heavy metals and sulfides, reduce environmental pollution, and improve the resource utilization rate of the steel slag. Among them, the water reducer is methacrylic acid. Steel slag particles of various particle sizes can be embedded with each other, which is helpful to improve the overall density of the mixture. After mixing, a more complex skeleton structure can be formed, which is helpful to improve the bearing capacity and stability of the water-stabilizing layer filler. The crushed steel slag particles are carbonized, so that the active ingredients in the steel slag, such as calcium oxide, react with carbon dioxide to form calcium carbonate, thereby improving the stability and durability of the steel slag. The calcium carbonate generated during the carbonization process fills the gaps between the steel slag particles, increases the density of the material, and improves its compressive strength and flexural strength. During the carbonization treatment, the surface tension of water can be reduced by spraying the water reducer on the surface of the steel slag particles, making it easier for water to penetrate between the steel slag particles. Among them, when the steel carbonized particles are dried and ball-milled, the particles of various particle sizes can be effectively separated by the classifier, improving the grinding efficiency and particle uniformity, so as to achieve higher-precision grinding and improve the uniformity and sphericity of the particles.
[0042] S2. Modification of steel slag
[0043] The steel carbide particles after ball milling, deionized water and fly ash were mixed in a mass ratio of 2:0.5:0.25, and stirred and mixed at a rate of 100 rpm for 10 hours, granulated and dried to obtain steel carbide green balls, wherein the temperature of the deionized water was 60°C, and then, anhydrous ethanol, expanded glass microspheres and steel carbide green balls were mixed uniformly in a mass ratio of 1:0.6:1, and at the same time, MPS was added dropwise at a rate of 3 ml / min, and then ammonia water was added to adjust the pH to 7.5, and mechanical stirring was performed at room temperature. Stir for 9 hours, and heat at 120°C for 1 hour, then, after repeated alcohol washing twice, centrifuge at 9000r / min for 20 minutes, freeze-dry, obtain steel slag modified particles, and mix the steel slag modified particles, silicone oil and methyl methacrylate in a weight ratio of 1:3:4 to form a first premix, then, mix deionized water, sodium dodecylbenzene sulfonate and sodium bicarbonate in a weight ratio of 8:3:0.2 to form a second premix, and then, The first premix and the second premix were mixed in a weight ratio of 1:2, and then emulsified at room temperature for 2 hours, and then ultrasonically finely emulsified for 20 minutes, and 1wt% of azobisisobutyronitrile was added thereto, stirred evenly, and placed in a water bath at 80°C for 2 hours, and cooled to room temperature to obtain steel slag composite particles; the steel carbonized particles after ball milling were mixed with deionized water and fly ash, wherein the deionized water can prevent the steel carbonized particles from further hydration, thereby reducing the expansion of the steel slag, improving the volume stability of the steel slag, and the powder After fly ash pretreatment, coal ash steel slag will generate needle-shaped and spatial network products. At the same time, the products are wrapped on the surface of steel slag to form a protective layer, which further reduces the expansion of steel slag. Through silane coupling agent, chemical bond bridges can be formed between steel carbonization green balls and expanded glass microspheres, thereby improving the compatibility and bonding strength of the two. At the same time, the expanded glass microspheres can form an open pore structure in the steel carbonization green balls. These pores provide channels for moisture, allowing moisture to pass through the steel slag composite particles, thereby improving the overall permeability of the road water-stabilizing layer filler.
[0044] S3. Preparation of filler
[0045] According to weight parts, 35 parts of steel slag composite particles, 5 parts of cement, 5 parts of granite powder, 3 parts of lime and 30 parts of water were mixed until uniform, and heated at a temperature of 160° C. for 3 hours to obtain a filler blank, and then the temperature was raised to 200° C. At the same time, 1 part of polyvinyl alcohol was added to the filler blank, and sheared for 10 minutes to obtain a filler pre-finished product;
[0046] S4, Forming and Compacting
[0047] The wheel rolling method is adopted to pre-press the filler pre-finished product 4 times, and finally, the direction is changed and rolled 5 times to obtain the filler finished product.
[0048] Example 2
[0049] A method for preparing a road water-stabilizing layer filler based on steel slag recycling comprises the following steps:
[0050] S1. Pretreatment of slag
[0051] The steel slag was first rinsed with tap water and then dried to obtain a clean steel slag base material. The steel slag base material was crushed by a crusher, and steel slag particles with particle sizes of 1 mm, 2 mm, and 3.5 mm were taken using a vibrating screen. The surface of the steel slag particles in each particle size range was sprayed with a water reducer, and then placed in a carbonization box. When the vacuum degree was -0.25 MPa, CO2 gas was introduced until the pressure in the carbonization box reached 0.25 MPa. The carbonization treatment was performed for 48 hours to obtain steel carbonized particles. Then, the steel carbonized particles were dried and ball-milled until the specific surface area of the steel carbonized particles was 170 m 2 / kg, washing the steel slag can remove harmful substances in the steel slag, such as heavy metals and sulfides, reduce environmental pollution, and improve the resource utilization rate of the steel slag. Among them, the water reducer is methacrylic acid. Steel slag particles of various particle sizes can be embedded with each other, which is helpful to improve the overall density of the mixture. After mixing, a more complex skeleton structure can be formed, which is helpful to improve the bearing capacity and stability of the water-stabilizing layer filler. The crushed steel slag particles are carbonized, so that the active ingredients in the steel slag, such as calcium oxide, react with carbon dioxide to form calcium carbonate, thereby improving the stability and durability of the steel slag. The calcium carbonate generated during the carbonization process fills the gaps between the steel slag particles, increases the density of the material, and improves its compressive strength and flexural strength. During the carbonization treatment, the surface tension of water can be reduced by spraying the water reducer on the surface of the steel slag particles, making it easier for water to penetrate between the steel slag particles. Among them, when the steel carbonized particles are dried and ball-milled, the particles of various particle sizes can be effectively separated by the classifier, improving the grinding efficiency and particle uniformity, so as to achieve higher-precision grinding and improve the uniformity and sphericity of the particles.
[0052] S2. Modification of steel slag
[0053] The steel carbonized particles after ball milling, deionized water and fly ash were mixed in a mass ratio of 2:0.8:0.25, and stirred and mixed at a rate of 130 rpm for 13 hours, granulated and dried to obtain steel carbonized green balls, wherein the temperature of the deionized water was 75°C, and then, anhydrous ethanol, expanded glass microspheres and steel carbonized green balls were mixed uniformly in a mass ratio of 1:0.6:1, and at the same time, ODMS was added dropwise at a rate of 4 ml / min, and then ammonia water was added to adjust the pH to 7.8, and mechanical stirring was performed at room temperature. The mixture was stirred for 9.5 hours and heated at 135°C for 1.5 hours. After repeated alcohol washing for 3 times, the mixture was centrifuged at 9300 r / min for 25 minutes. After freeze drying, the slag modified particles were obtained. The slag modified particles, silicone oil and methyl methacrylate were mixed uniformly in a weight ratio of 1:3:4 to form a first premix. Then, deionized water, sodium dodecylbenzene sulfonate and sodium bicarbonate were mixed uniformly in a weight ratio of 8:3:0.2 to form a second premix. Then, the first premix and the second premix are mixed, emulsified at room temperature for 2.5 hours, and then ultrasonically finely emulsified for 23 minutes, and 1.3wt% of azobisisobutyronitrile is added thereto, stirred evenly, and water-bathed at 83°C for 2.5 hours, and cooled to room temperature to obtain steel slag composite particles; the steel carbonized particles after ball milling are mixed with deionized water and fly ash, wherein the deionized water can prevent the steel carbonized particles from further hydration, thereby reducing the expansion of the steel slag and improving the volume stability of the steel slag, and After fly ash pretreatment, fly ash steel slag will generate needle-shaped and spatial network products. At the same time, the products are wrapped on the surface of steel slag to form a protective layer, which further reduces the expansion of steel slag. Through the silane coupling agent, a chemical bond bridge can be formed between the steel carbonization green ball and the expanded glass microspheres, thereby improving the compatibility and bonding strength of the two. At the same time, the expanded glass microspheres can form an open pore structure in the steel carbonization green ball. These pores provide channels for moisture, allowing moisture to pass through the steel slag composite particles, thereby improving the overall permeability of the road water-stabilizing layer filler.
[0054] S3. Preparation of filler
[0055] According to weight parts, 50 parts of steel slag composite particles, 10 parts of cement, 9 parts of granite powder, 4 parts of lime, and 33 parts of water were mixed until uniform, and heated at a temperature of 165° C. for 4 hours to obtain a filler blank, and then the temperature was raised to 210° C., and at the same time, 1.5 parts of polyvinyl alcohol was added to the filler blank, and sheared for 13 minutes to obtain a filler pre-finished product;
[0056] S4, Forming and Compacting
[0057] The wheel rolling method is adopted to pre-press the filler pre-finished product 4 times, and finally, the direction is changed and rolled 8 times to obtain the filler finished product.
[0058] Example 3
[0059] A method for preparing a road water-stabilizing layer filler based on steel slag recycling comprises the following steps:
[0060] S1. Pretreatment of slag
[0061] The steel slag was first rinsed with tap water and then dried to obtain a clean steel slag base material. The steel slag base material was crushed by a crusher, and steel slag particles with particle sizes of 1.5 mm, 2.5 mm, and 4 mm were taken using a vibrating screen. The surface of the steel slag particles in each particle size range was sprayed with a water reducer, and then placed in a carbonization box. When the vacuum degree was -0.25 MPa, CO2 gas was introduced until the pressure in the carbonization box reached 0.25 MPa. The carbonization treatment was performed for 50 hours to obtain steel carbonized particles. Then, the steel carbonized particles were dried and ball-milled until the specific surface area of the steel carbonized particles was 180 m 2 / kg, washing the steel slag can remove harmful substances in the steel slag, such as heavy metals and sulfides, reduce environmental pollution, and improve the resource utilization rate of the steel slag. Among them, the water reducer is methacrylic acid. Steel slag particles of various particle sizes can be embedded with each other, which is helpful to improve the overall density of the mixture. After mixing, a more complex skeleton structure can be formed, which is helpful to improve the bearing capacity and stability of the water-stabilizing layer filler. The crushed steel slag particles are carbonized, so that the active ingredients in the steel slag, such as calcium oxide, react with carbon dioxide to form calcium carbonate, thereby improving the stability and durability of the steel slag. The calcium carbonate generated during the carbonization process fills the gaps between the steel slag particles, increases the density of the material, and improves its compressive strength and flexural strength. During the carbonization treatment, the surface tension of water can be reduced by spraying the water reducer on the surface of the steel slag particles, making it easier for water to penetrate between the steel slag particles. Among them, when the steel carbonized particles are dried and ball-milled, the particles of various particle sizes can be effectively separated by the classifier, improving the grinding efficiency and particle uniformity, so as to achieve higher-precision grinding and improve the uniformity and sphericity of the particles.
[0062] S2. Modification of steel slag
[0063] The steel carbonized particles after ball milling, deionized water and fly ash were mixed in a mass ratio of 2:1:0.25, and stirred and mixed at a rate of 150rpm for 15h, granulated and dried to obtain steel carbonized green balls, wherein the temperature of the deionized water was 90°C, and then, anhydrous ethanol, expanded glass microspheres and steel carbonized green balls were mixed uniformly in a mass ratio of 1:0.6:1, and at the same time, ODMS was added dropwise at a rate of 5ml / min, and then ammonia water was added, the pH was adjusted to 8, and mechanical stirring was performed at room temperature. 10h, and heated at 150°C for 2h, then, after repeated alcohol washing 4 times, centrifuged at 9500r / min for 30min, freeze-dried to obtain steel slag modified particles, steel slag modified particles, silicone oil and methyl methacrylate were mixed uniformly in a weight ratio of 1:3:4 to form a first premix, then deionized water, sodium dodecylbenzene sulfonate and sodium bicarbonate were mixed uniformly in a weight ratio of 8:3:0.2 to form a second premix, and then After that, the first premix and the second premix are mixed, emulsified at room temperature for 3 hours, and then ultrasonically finely emulsified for 25 minutes, and 1.5wt% of azobisisobutyronitrile is added thereto, stirred evenly, and water-bathed at 85°C for 3 hours, and cooled to room temperature to obtain steel slag composite particles; the steel carbonized particles after ball milling are mixed with deionized water and fly ash, wherein the deionized water can prevent the steel carbonized particles from further hydration, thereby reducing the expansion of the steel slag, improving the volume stability of the steel slag, and the fly ash After being pretreated with fly ash, steel slag will generate needle-shaped and spatial network products. At the same time, the products are wrapped on the surface of steel slag to form a protective layer, which further reduces the expansion of steel slag. Through the silane coupling agent, a chemical bond bridge can be formed between the steel carbonized green balls and the expanded glass microspheres, thereby improving the compatibility and bonding strength of the two. At the same time, the expanded glass microspheres can form an open pore structure in the steel carbonized green balls. These pores provide channels for moisture, allowing moisture to pass through the steel slag composite particles, thereby improving the overall permeability of the road water-stabilizing layer filler.
[0064] S3. Preparation of filler
[0065] According to weight parts, 60 parts of steel slag composite particles, 15 parts of cement, 15 parts of granite powder, 5 parts of lime, and 50 parts of water were mixed until uniform, and heated at a temperature of 170° C. for 5 hours to obtain a filler blank, and then the temperature was raised to 220° C. At the same time, 2 parts of polyvinyl alcohol were added to the filler blank, and sheared for 15 minutes to obtain a filler pre-finished product;
[0066] S4, Forming and Compacting
[0067] The wheel rolling method is adopted to pre-press the filler pre-finished product 5 times, and finally, the direction is changed and rolled 10 times to obtain the filler finished product.
[0068] The water expansion rate of steel carbide particles was tested at room temperature and deionized water at 60°C, 75°C, and 90°C in Examples 1-3 for 2d, 5d, 10d, and 15d, and the change law of steel slag expansion under different water bath conditions was determined; and the change law of steel slag expansion under different water bath conditions was obtained by curve equation fitting, and a parameter table of the change law of expansion of steel carbide particles under different water bath conditions was obtained, as shown in Table 1:
[0069] Table 1: Parameter table of the change of expansion of steel carbonized particles under the conditions of room temperature and deionized water at the temperature of Examples 1-3
[0070]
[0071] Through the data analysis of Table 1, it is found that, taking the immersion age of 15 days as an example, the reduction effect of immersion at room temperature is the worst, and the expansion rate is still 0.55%. When the water temperature of 60°C in Example 1 is used, the expansion rate of the steel carburized particles is reduced by 0.1% compared with that at room temperature. When the water temperature of 75°C in Example 2 is used, the expansion rate of the steel carburized particles is reduced by 0.25% compared with 60°C. When the water temperature of 90°C in Example 3 is used, the expansion rate of the steel carburized particles is the lowest, which is 0.03%, and the effect of reducing the expansibility is significant. In summary, the effect of temperature on the expansibility is more significant. Under the actual permitted conditions, the temperature should be increased as much as possible to improve the expansion rate of the steel carburized particles, and the 90°C deionized water in Example 3 is the best.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 3 is that:
[0074] In step S3, a microwave + far infrared combined heating method is used for the mixture of steel slag composite particles, cement, granite powder, lime and water, wherein the microwave + far infrared combination is performed in an intermittent heating manner. During the heating process, a built-in stirring device is used to stir the mixture to ensure that the mixture is heated unevenly inside and outside. In order to make the mixture evenly distributed in the microwave heating device and the far infrared heating device, an automatic feeding system, such as a screw conveyor, a belt conveyor or a vibrating feeder, is used to control the feed rate of the mixture to 25 g / s;
[0075] The intermittent heating process is: heating with microwave for 35 seconds, cooling with a heat exchanger for 2 minutes, heating with far-infrared for 40 seconds, cooling with a heat exchanger for 2 minutes, this is one cycle, and the operation is repeated 3 times until the mixture of steel slag composite particles, cement, granite powder, lime and water is heated to 120°C, and finally, kept warm for 30 minutes. The microwave heating equipment and far-infrared heating equipment used are all existing technologies; the microwave frequency is 2.35GHz, the far-infrared wavelength is 50μm, and the heating time is 1.2h.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 3 is that:
[0078] In step S3, a microwave + far infrared combined heating method is used for the mixture of steel slag composite particles, cement, granite powder, lime and water, wherein the microwave + far infrared combination is performed in an intermittent heating manner. During the heating process, a built-in stirring device is used to stir the mixture to ensure that the mixture is heated unevenly inside and outside. In order to make the mixture evenly distributed in the microwave heating device and the far infrared heating device, an automatic feeding system, such as a screw conveyor, a belt conveyor or a vibrating feeder, is used to control the feeding rate of the mixture to 28 g / s;
[0079] The intermittent heating process is: heating with microwave for 38 seconds, cooling with a heat exchanger for 2.5 minutes, heating with far-infrared for 43 seconds, cooling with a heat exchanger for 2.5 minutes, this is one cycle, and the operation is repeated 4 times until the mixture of steel slag composite particles, cement, granite powder, lime and water is heated to 130°C, and finally, kept warm for 33 minutes. The microwave heating equipment and far-infrared heating equipment used are all existing technologies; the microwave frequency is 2.4 GHz, the far-infrared wavelength is 60 μm, and the heating time is 1.3 hours.
[0080] Example 6
[0081] The difference between this embodiment and embodiment 3 is that:
[0082] In step S3, a microwave + far infrared combined heating method is used for the mixture of steel slag composite particles, cement, granite powder, lime and water, wherein the microwave + far infrared combination is performed in an intermittent heating manner. During the heating process, a built-in stirring device is used to stir the mixture to ensure that the mixture is heated unevenly inside and outside. In order to make the mixture evenly distributed in the microwave heating device and the far infrared heating device, an automatic feeding system, such as a screw conveyor, a belt conveyor or a vibrating feeder, is used to control the feeding rate of the mixture to 30 g / s;
[0083] The intermittent heating process is: heating with microwave for 40 seconds, cooling with a heat exchanger for 3 minutes, heating with far-infrared for 45 seconds, cooling with a heat exchanger for 3 minutes, this is one cycle, and the operation is repeated 4 times until the mixture of steel slag composite particles, cement, granite powder, lime and water is heated to 140°C, and finally, kept warm for 35 minutes. The microwave heating equipment and far-infrared heating equipment used are all existing technologies; the microwave frequency is 2.45GHz, the far-infrared wavelength is 80μm, and the heating time is 1.5h.
[0084] On the basis of Example 3, the mixture of steel slag composite particles, cement, granite powder, lime and water was treated and prepared by the microwave + far-infrared combined heating method of Examples 4-6, and a pavement material strength tester was used to carry out an unconfined compressive strength test on the road water-stabilizing layer filler, wherein the unconfined compressive strength was calculated according to formula (1-1).
[0085]
[0086] Where: R C is the unconfined compressive strength (MPa), P is the maximum pressure of the specimen failure (N), A is the cross-sectional area of the specimen (mm), and A is calculated according to formula (1-2);
[0087]
[0088] Where: D is the diameter of the specimen (mm).
[0089] The unconfined compressive strength data of the road water-stabilizing layer filler were obtained, and the test results were recorded in Table 2.
[0090] Table 2: Unconfined compressive strength of road water-stabilizing layer filler made from the mixture treated by the heating method of Examples 4-6
[0091] Example 4 Example 5 Example 6 <![CDATA[R C / MPa]]> 4.05 4.84 6.46
[0092] Through the data analysis of Table 2, it is found that the road water-stabilizing layer filler prepared by treating the mixture of steel slag composite particles, cement, granite powder, lime and water respectively using the microwave + far-infrared combined heating method of Example 6 has the largest unconfined compressive strength, while the unconfined compressive strength of the road water-stabilizing layer filler corresponding to the heating method of Example 5 is second, and the unconfined compressive strength of the road water-stabilizing layer filler corresponding to the heating method of Example 4 is the smallest. There is a close relationship between the generation of cracks in the road water-stabilizing layer filler and the unconfined compressive strength. Under normal circumstances, when the unconfined compressive strength of the filler is not enough to resist the effects of external loads or environmental factors (such as temperature changes, humidity changes, chemical erosion, etc.), cracks may occur. Therefore, the microwave + far-infrared combined heating method of Example 6 is best for reducing cracks.
[0093] Example 7
[0094] The difference between this embodiment and embodiment 6 is that:
[0095] In step S4, the filler pre-finished product is subjected to curing treatment before pre-pressing, and the curing process is as follows:
[0096] S4-1, curing the filler blank at a temperature of 30°C for 12 hours;
[0097] S4-2, using steam curing, curing temperature of 95 ° C, curing time of 3 hours, and then performing room temperature curing process again, and controlling the curing time to be 5 hours, repeating the steam curing process, and curing alternately twice to obtain a filler curing product, wherein the steam heating rate is 4 ° C / min, and before steam curing, the temperature of the filler pre-finished product should be increased to close to the steam temperature, which can reduce the thermal shock caused by temperature mutation. At the same time, before the filler blank after room temperature curing enters the high-temperature steam environment, ensure that the humidity of the filler pre-finished product matches the steam curing environment to avoid shrinkage or expansion problems caused by humidity differences;
[0098] S4-3, spray water on the finished filler curing product for 6 hours, and the amount of water sprayed is 12% of the weight of the finished filler curing product, and finally air-dry.
[0099] Example 8
[0100] The difference between this embodiment and embodiment 6 is that:
[0101] In step S4, the filler pre-finished product is subjected to curing treatment before pre-pressing, and the curing process is as follows:
[0102] S4-1, curing the filler blank at a temperature of 33°C for 12.5 hours;
[0103] S4-2, using steam curing, the curing temperature is 98°C, the curing time is 3.5h, and then the normal temperature curing process is performed again, and the curing time is controlled to be 5.5h, and the steam curing process is repeated, and the curing is alternately performed for 3 times to obtain a curing filler product, wherein the steam heating rate is 4.5°C / min. Before steam curing, the temperature of the filler pre-finished product should be increased to close to the steam temperature, which can reduce the thermal shock caused by the sudden change in temperature. At the same time, before the filler blank after normal temperature curing enters the high-temperature steam environment, ensure that the humidity of the filler pre-finished product matches the steam curing environment to avoid shrinkage or expansion problems caused by humidity differences;
[0104] S4-3, spray water on the finished filler curing product for 6.5 hours, and the amount of water sprayed is 12.5% of the weight of the finished filler curing product, and finally air-dry.
[0105] Example 9
[0106] The difference between this embodiment and embodiment 6 is that:
[0107] In step S4, the filler pre-finished product is subjected to curing treatment before pre-pressing, and the curing process is as follows:
[0108] S4-1, curing the filler blank at a temperature of 35°C for 13 hours;
[0109] S4-2, using steam curing, curing temperature of 100 ° C, curing time of 4 hours, and then performing room temperature curing process again, and controlling the curing time to 6 hours, repeating the steam curing process, and curing alternately for 3 times to obtain a filler curing product, wherein the steam heating rate is 5 ° C / min, and before steam curing, the temperature of the filler pre-finished product should be increased to close to the steam temperature, which can reduce the thermal shock caused by temperature mutation. At the same time, before the filler blank after room temperature curing enters the high-temperature steam environment, ensure that the humidity of the filler pre-finished product matches the steam curing environment to avoid shrinkage or expansion problems caused by humidity differences;
[0110] S4-3, spray water on the finished filler curing product for 7 hours, and the amount of water sprayed is 13% of the weight of the finished filler curing product, and finally air-dry.
[0111] On the basis of Example 6, the unconfined compressive strength test of the road water-stabilizing layer filler was carried out on the filler pre-finished products that had undergone the maintenance treatment of Examples 7-9 using a pavement material strength tester, wherein the unconfined compressive strength was calculated according to formula (1-1).
[0112] Example 7 Example 8 Example 9 <![CDATA[R C / MPa]]> 7.52 7.68 8.03
[0113] Through the data analysis of Table 2, it is found that after the filler pre-finished product is treated by the curing method of Example 9, the unconfined compressive strength of the filler pre-finished product is the largest, and after the filler pre-finished product is treated by the curing method of Example 8, the unconfined compressive strength of the filler pre-finished product is second, and after the filler pre-finished product is treated by the curing method of Example 7, the unconfined compressive strength of the filler pre-finished product is the smallest. Therefore, the curing method of Example 9 has the best effect on reducing cracks, and therefore, Example 9 is the best embodiment.
Claims
1. A method for preparing road water-stabilizing layer filler based on steel slag recycling, characterized in that: The following steps are involved: S1. Pretreatment of slag First, the steel slag is washed with tap water, and then dried to obtain clean steel slag base material. After the steel slag base material is crushed by a crusher, it is placed in a carbonization box for carbonization treatment for 45-50 hours to obtain steel carbonized particles. Then, the steel carbonized particles are dried and ball-milled until the specific surface area of the steel carbonized particles is 150-180m 2 / kg; S2. Modification of steel slag The steel carbonized particles after ball milling, deionized water and fly ash are mixed, granulated and dried in a mass ratio of 2:0.5 to 1:0.25 to obtain steel carbonized green balls; anhydrous ethanol, expanded glass microspheres and steel carbonized green balls are uniformly mixed in a mass ratio of 1:0.6:1, and 1.2-1.5wt% silane coupling agent is added thereto; the pH is adjusted to 7.5-8, and the mixture is heated and freeze-dried to obtain steel slag modified particles; then, the steel slag modified particles, silicone oil and methyl methacrylate are mixed in a weight ratio of 1:3:4 to obtain steel slag modified particles; methyl acrylate is mixed evenly to form a first premix, then, deionized water, sodium dodecylbenzene sulfonate and sodium bicarbonate are mixed evenly in a weight ratio of 8:3:0.2 to form a second premix, and then, the first premix and the second premix are mixed in a weight ratio of 1:2, ultrasonic fine emulsification is performed at room temperature for 20-25 minutes, and 1-1.5wt% of azobisisobutyronitrile is added thereto, stirred evenly, and placed in a water bath at a temperature of 80-85°C for 2-3 hours, and cooled to room temperature to obtain steel slag composite particles; S3. Preparation of filler According to weight parts, 35-60 parts of steel slag composite particles, 5-15 parts of cement, 5-15 parts of granite powder, 3-5 parts of lime, and 30-50 parts of water are mixed until uniform, and heated at a temperature of 160-170° C. for 3-5 hours to obtain a filler blank, and then the temperature is raised to 200-220° C. At the same time, 1-2 parts of stabilizer are added to the filler blank, and sheared for 10-15 minutes to obtain a filler pre-finished product; S4, Forming and Compacting The wheel rolling method is adopted to pre-press the filler pre-finished product 4-5 times, and finally, the direction is changed and rolled 5-10 times to obtain the filler finished product.
2. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 1, characterized in that: In step S1, the steel slag base material is crushed by a crusher, and then a vibrating screen is used to take steel slag particles with particle sizes in the ranges of 0.5-1.5 mm, 1.6-2.5 mm, and 2.6-4 mm, respectively. After spraying a water reducer on the surface of the steel slag particles in each particle size range, the particles are placed in a carbonization box. When the vacuum degree is -0.25 MPa, CO2 gas is introduced until the pressure in the carbonization box reaches 0.25 MPa, and then carbonization treatment is performed to obtain steel carbonized particles.
3. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 2 is characterized in that: The water reducer is a polycarboxylic acid water reducer, which is selected from one of methacrylic acid, acrylic acid, acrylamide or hydroxypropyl methylcellulose.
4. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 1, characterized in that: In step S2, the temperature of the deionized water is 60-90° C., and the silane coupling agent is MPS or ODMS.
5. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 1, characterized in that: In step S3, a mixture of steel slag composite particles, cement, granite powder, lime and water is heated by a microwave + far infrared combination method, wherein the microwave + far infrared combination is performed in an intermittent heating manner.
6. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 5 is characterized in that: The intermittent heating process is: heating with microwave for 35-40 seconds, cooling with heat exchanger for 2-3 minutes, heating with far infrared for 40-45 seconds, cooling with heat exchanger for 2-3 minutes, this is one cycle, and the operation is repeated 3-4 times until the mixture of steel slag composite particles, cement, granite powder, lime and water is heated to 120-140° C., and finally, it is kept warm for 30-35 minutes.
7. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 6 is characterized in that: The microwave frequency is 2.35-2.45 GHz, the far infrared wavelength is 50-80 μm, and the heating time is 1.2-1.5 h.
8. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 1, characterized in that: In step S4, the filler pre-finished product is subjected to curing treatment before pre-pressing, and the curing process is as follows: S4-1, curing the filler blank at a temperature of 30-35°C for 12-13 hours; S4-2, using steam curing, the curing temperature is 95-100 ° C, the curing time is 3-4 hours, and the room temperature curing process is performed again, and the curing time is controlled to be 5-6 hours, and the steam curing process is repeated, and the curing is alternately performed 2-3 times to obtain a finished curing filler product; S4-3, spray water on the filler curing product for 6-7 hours, and the amount of water sprayed is 12-13% of the weight of the filler curing product, and finally air-dry.
9. The method for preparing road water-stabilizing layer filler based on steel slag recycling according to claim 8, characterized in that: When steam curing is performed in step S4-2, the steam heating rate is 4-5°C / min.
Citation Information
Patent Citations
Steel slag and cement stabilized base material
CN102491703A
Modified steel slag alcohol-based casting coating and making method thereof
CN104084529A
Steel slag powder water stabilized base material and preparation method thereof
CN104529318A
Dense grade asphalt mixture prepared from modified steel slag and preparation method of asphalt mixture
CN110156380A
Thermal insulation building material prepared from amino modified SiO2 aerogel in cooperation with solid waste carbonization and method
CN112456944A
Cited By
Freeze-thaw resistant soft soil curing agent and preparation method thereof
CN119912212A
